Molecular characterization and fruiting efficiency of Calocybe indica strains - Kaur, Gagandeep; Johl, P P; Sodhi, H S; Kapoor, S (Mushroom Research, 2015)
Calocybe indica is a tropical mushroom with milky white sporocarp. It holds a promising future due to its consumer acceptability and comparable nutritive value. Present study was conducted on seven strains of C. indica designated as Ci-2 to Ci-6, Ci-9 and APK II. Molecular diversity between strains was studied using Random Amplified Polymorphic DNA (RAPD) analysis of the genomic DNA with eight primers. Diversity among the strains was found to a level of 7.13% with a coefficient of similarity ranging from 0.60 to 0.81. Strains were also evaluated for their yield potential on wheat straw, paddy straw and their combination (1:1). Maximum yield 88.38 kg q was obtained in the strain Ci-3 on hot water treated wheat straw. On wheat straw + paddy straw (1:1) also the yield harvest was the maximum for Ci-3 followed by Ci-5 and APK II (58.76 to 60.84 kg q-1). The number of fruit bodies ranged from 400 to 1014 with an average weight ranging between 50 to 98 g. The pileus diameter ranged from 4.8 to 10.6 cm, total length 12.3 to 20.0 cm and stipe length was observed in the range of 9.9 to 17.4 cm.